2006
DOI: 10.1111/j.1442-200x.2006.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Urease activity does not reflect the degree of colonization by Helicobacter pylori in children

Abstract: The 13C-UBT does not estimate the severity of histological findings in children with Helicobacter pylori infection. The results of the breath test should be interpreted in a qualitative way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Additionally, some authors have shown a significant correlation of 13 C-UBT values with activity of gastritis [37,38,39,40] and pepsinogen I/II ratio [40]. However, other reports suggest that 13 C-UBT is not an appropriate tool for assessment of bacterial load [44,45,46,47]. Given the broad variety of protocols and varying sensitivity and specificity of the method, this discrepancy can be explained by the lack of comparability standards among the studies (table 4).…”
Section: C-urease Breath Test Results In Relation To H Pylori Densimentioning
confidence: 99%
“…Additionally, some authors have shown a significant correlation of 13 C-UBT values with activity of gastritis [37,38,39,40] and pepsinogen I/II ratio [40]. However, other reports suggest that 13 C-UBT is not an appropriate tool for assessment of bacterial load [44,45,46,47]. Given the broad variety of protocols and varying sensitivity and specificity of the method, this discrepancy can be explained by the lack of comparability standards among the studies (table 4).…”
Section: C-urease Breath Test Results In Relation To H Pylori Densimentioning
confidence: 99%
“…No mammalian tissue is known to produce urease and is unable to metabolize urea 29 . Thus, in H. pylori negative persons, oropharyngeal urease is the only source of breath 14 CO 2 after ingestion of 14 C‐urea.…”
Section: Discussionmentioning
confidence: 99%
“…No mammalian tissue is known to produce urease and is unable to metabolize urea. 29 Thus, in H. pylori negative persons, oropharyngeal urease is the only source of breath 14 CO2 after ingestion of 14 C-urea. Given the clinical importance of H. pylori, there is need for its prompt and accurate diagnosis followed by eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Graham et al also observed 33% negative UBTs after 6.5 days of PPI treatment and acidification of the stomach with citric acid did not improve the results [ 87 ]. On the other hand, false-positives may be due to contamination with non- H. pylori urease-producing bacteria [ 88 , 89 ]. Sano et al demonstrated that urease activity was also present in the oropharynx, therefore gurgling to eliminate urease-positive bacteria in the oropharynx and oral cavity is recommended [ 90 ].…”
Section: Indirect Diagnosismentioning
confidence: 99%